Mandibular second premolars with three root canals: A review and 3 case reports - Zahra Borna; Saeed Rahimi; Shahriar Shahi; Vahid Zand (Iranian Association of Endodontists; Iranian Center for Endodontic Research, 2011)
ABSTRACT: Before initiating any endodontic therapy, probability of extra canals should be considered. The Incidence of three canals in mandibular second premolar has been reported to be 0.46-0.5%. The present report describes nonsurgical endodontic treatment of three mandibular second premolars with three canals. In these cases, three orifices were located in mesiobuccal, distobuccal and lingual. Mesiobuccal orifices were found after removing dentinal shelves. Even in teeth with extremely complex root canal morphologies, conventional endodontic treatment without surgical intervention can result in adequate healing, as in these cases. Clinicians should be aware of unusual root canal anatomy in mandibular premolars. Very careful examination of the pulpal space, preferably with an optical device is recommended to locate any unusual orifices.